(untitled) (Brazilian Journal of Radiation Sciences (BJRS), 2022)
Radiotherapy (RT) plays an important role in the treatment of patients with head and neck cancer. Clinical changes in the surrounding healthy tissue are often inevitable. The deleterious effects on the bones of the jaws have been considered a contraindication for rehabilitation with dental implants. However, in recent years, the installation of implants in irradiated patients has been consolidated as a valuable treatment option. The aim of this study was to evaluate the effect of RT on the survival of osseointegrated dental implants in patients with head and neck cancer. The applied methodology involved an electronic search in the MEDLINE database during the last five years. We identified 67 scientific documents related to the keywords: "radiotherapy", "dental implants" and "head and neck cancer", four articles were selected and reviewed, composing this analysis. It is concluded that dental implants installed in irradiated bone in the oral cavity have a high survival rate, 97.37%, provided that rigorous monitoring is instituted in RT in order to be successful in the long term. The percentage of dental implant failures tended to be higher in the group of irradiated patients.